2017
DOI: 10.1016/j.yjmcc.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Intralipid protects the heart in late pregnancy against ischemia/reperfusion injury via Caveolin2/STAT3/GSK-3β pathway

Abstract: Background We recently demonstrated that the heart of late pregnant (LP) rodents is more prone to ischemia/reperfusion (I/R) injury compared to non-pregnant rodents. Lipids, particularly polyunsaturated fatty acids, have received special attention in the field of cardiovascular research. Here, we explored whether Intralipid (ITLD) protects the heart against I/R injury in LP rodents and investigated the mechanisms underlying this protection. Methods and Results In-vivo female LP rat hearts or ex-vivo isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 53 publications
(70 reference statements)
1
35
0
Order By: Relevance
“…In particular, propofol, a widely used anesthetic, has shown potential as a novel organ-protective agent through its efficient membrane-targeted and cytoprotective effects [4]. This is not surprising since lipid emulsions are major components of propofol, which accumulating data show provide organ protective effects against IR injury in many organs, such as the heart, kidney, liver, and intestines [6-13]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, propofol, a widely used anesthetic, has shown potential as a novel organ-protective agent through its efficient membrane-targeted and cytoprotective effects [4]. This is not surprising since lipid emulsions are major components of propofol, which accumulating data show provide organ protective effects against IR injury in many organs, such as the heart, kidney, liver, and intestines [6-13]. …”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate kinase isoform M2 (PKM2), which is known to regulate cell apoptosis in the liver, is a direct target of miR122. The obtained data showed that Pyruvate kinase isoform M2(as a cell apoptosis regulator in the liver) and caspase 3 were 2 targets of miR122 since the expression of Pyruvate kinase isoform M2 and capase-3 in the heats subjected to ischemia/reperfusion injury was significantly lower in intralipid group compared to control group in late pregnancy [17] .…”
Section: Intralipid In Heart Protectionmentioning
confidence: 95%
“…Researchers investigating the effect of miRNA during the administration of Intralipid found that Intralipid was able to affect apoptosis via miRNA (6,(11)(12).…”
Section: Ischemia-reperfusionmentioning
confidence: 99%
“…They proposed the theory of the lipid sink and hypothesized that lipid emulsions form a lipid compartment entrapping bupivacaine (2,3). The Eghbali research group demonstrated multiple cardioprotective effects of Intralipid against ischemia-reperfusion injury (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The exact mechanism of action of lipid emulsion has not yet been elucidated, but accumulating evidence suggests multimodal effects exist (4).…”
Section: Introductionmentioning
confidence: 99%